Educational Leadership Concepts in Hadith Mas'ūliyyah and Gundul-Gundul Pacul ; A Weberian Perspective - Muhammad Rijal Mushthofa; Nuri Safitri; Masruhan Masruhan (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study examines leadership ethics through the integration of hadith mas’uliyah, Max Weber’s theory of authority, and the philosophical values of the Javanese traditional song Gundul-Gundul Pacul. Previous studies generally discuss Islamic leadership, Weberian authority, and local wisdom separately without constructing an integrative framework among them. This research employs qualitative library research using descriptive-analytical and hermeneutic approaches. The findings reveal that both hadith mas’uliyah and Gundul-Gundul Pacul emphasize leadership as moral responsibility grounded in accountability, humility, and public service. Through Weber’s perspective, these traditions reflect traditional, charismatic, and rational-legal authority simultaneously. This study proposes the “Wakul Leadership Model” as a conceptual synthesis integrating Islamic ethics, sociological legitimacy, and Javanese local wisdom. The model contributes to the development of contextual and ethical leadership discourse in contemporary Indonesian society.